WAYS TO ENSURE SECURITY IN COMMERCIAL BANKS - Xanbabayev Maqsud Rashidovich (Journals Park Publishing, 2022)
In the article, proposals and recommendations on the nature of digital banking in the national economy, its application, current state and development analysis are considered. Also, features of digital banking development in commercial banks were considered.
Keywords: commercial banking, digital banking, digital banking, banking products, software.